National Green Export Review of Lebanon: Natural Soap and Ecotourism - United Nations Conference on Trade; Development (United Nations, 2020)
This report presents the findings of the Lebanon National Green Export Review (NGER) conducted between 2016 and 2018 through a partnership between the Lebanese Government and UNCTAD. It analyses green production and export opportunities in the natural soap and ecotourism sectors and comprises national action plans to develop green exports in each sector. The Lebanese olive oil sector is well established and very competitive with around 544 registered oil mills in Lebanon and 110,000 olive farmers and growers. Olive oil that is not of food quality is used to make soap thereby creating jobs and improving the income of local workers while contributing to the reduction of agricultural waste. The two main types of oil used for soap production are pomace oil, extracted the dregs of the olive paste, and olive oil unsuitable for consumption. The report was prepared by a team of national experts with technical support provided by UNCTAD.